1996
DOI: 10.1063/1.361782
|View full text |Cite
|
Sign up to set email alerts
|

Electron traps in Ca2+- or Sr2+-doped BaFBr:Eu2+ x-ray storage phosphors

Abstract: Holetrapping sites and the mechanism of the photostimulated luminescence of the xray storage phosphor RbI:Tl+

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 14 publications
2
11
0
Order By: Relevance
“…a high conversion efficiency of X-rays into photostimulable defects, it is desirable that the phosphors can be stimulated with low laser light intensity, particularly in the infrared spectral region. It was shown that the PSL excitation of BaFBr doped with Eu 2+ can be made sensitive to stimulation further into the infrared by additional Ca 2+ or Sr 2+ doping [54,64].…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
See 4 more Smart Citations
“…a high conversion efficiency of X-rays into photostimulable defects, it is desirable that the phosphors can be stimulated with low laser light intensity, particularly in the infrared spectral region. It was shown that the PSL excitation of BaFBr doped with Eu 2+ can be made sensitive to stimulation further into the infrared by additional Ca 2+ or Sr 2+ doping [54,64].…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
“…26). A more detailed investigation of the symmetry of the Ca 2+ perturbed F(Br --) centre was made with conventional ENDOR measurements [64].…”
Section: Generation Of Electron and Hole Trap Centresmentioning
confidence: 99%
See 3 more Smart Citations